Long‐term evaluation of mesenchymal stem cell therapy in a feline model of chronic allergic asthma. Issue 12 (December 2014) - Trzil, J. E.; Masseau, I.; Webb, T. L.; Chang, C.‐H.; Dodam, J. R.; Cohn, L. A.; Liu, H.; Quimby, J. M.; Dow, S. W.; Reinero, C. R.
Summary Background Mesenchymal stem cells (MSCs) decrease airway eosinophilia, airway hyperresponsiveness (AHR), and remodelling in murine models of acutely induced asthma. We hypothesized that MSCs would diminish these hallmark features in a chronic feline asthma model. Objective To document effects of allogeneic, adipose‐derived MSCs on airway inflammation, AHR, and remodelling over time and investigate mechanisms by which MSCs alter local and systemic immunologic responses in chronic experimental feline allergic asthma. Methods Cats with chronic, experimentally induced asthma received six intravenous infusions of MSCs (0.36–2.5 × 10E7 MSCs/infusion) or placebo bimonthly at the time of study enrollment. Cats were evaluated at baseline and longitudinally for 1 year. Outcome measures included: bronchoalveolar lavage fluid cytology to assess airway eosinophilia, pulmonary mechanics and clinical scoring to assess AHR, and thoracic computed tomographic (CT) scans to assess structural changes (airway remodelling). CT scans were evaluated using a scoring system for lung attenuation (LA) and bronchial wall thickening (BWT). To assess mechanisms of MSC action, immunologic assays including allergen‐specific IgE, cellular IL‐10 production, and allergen‐specific lymphocyte proliferation were performed. Results There were no differences between treatment groups or over time with respect to airway eosinophilia or AHR. However, significantly lower LA and BWT scores were noted in CT images of MSC‐treated animals compared to placebo‐treated cats at month 8 of the study (LA P = 0.0311; BWT P = 0.0489). No differences were noted between groups in the immunologic assays. Conclusions and Clinical Relevance When administered after development of chronic allergic feline asthma, MSCs failed to reduce airway inflammation and AHR. However, repeated administration of MSCs at the start of study did reduce computed tomographic measures of airway remodelling by month 8, although the effect was not sustained at month 12. Further study of MSC therapy including repeated MSC administration is warranted to assess impact on remodelling in chronic asthma.